Étudiants d'origine populaire et accès à l'université publique - Nadir Zago (Les éditions de la Maison des sciences de l'Homme, 2009)
Since the 1990s, Brazil has experienced a rapid expansion of higher education, but this expansion has gone hand in hand with a selection system for access to public universities producing high socio-economic and cultural inequalities. From interviews with 27 students from the State University Federal de Santa Catarina in southern Brazil, the article analyzes a number of conditions related to access and retention in higher education, and investment strategies of young lower classes who pass the entrance exam (vestibular) to public universities. While most students present school careers marked by good results, the low quality of education received generally makes problematic their access to university, as evidenced by the high demand for enrolment in courses preparatory to the examination. Furthermore, the necessity of having an income generating activity may influence their choice and delay their exams.